5,10-A2B2-Type meso-Substituted Porphyrins A Unique Class of Porphyrins with a Realigned Dipole Moment - SENGE, MATHIAS (My University, 2011)
Abstract: Current applications in porphyrin chemistry require the use of unsymmetrically substituted porphyrins. Many current industrial interests in optics and biomedicine require systems with either push-pull (electron donating and withdrawing groups) or amphiphilic systems (hydrophobic and hydrophilic groups). In this context we present the class of 5,10-A2B2-type porphyrins where two different substituents are positioned in diagonally opposite meso positions. Thus, the intramolecular dipole moment in these tetrapyrroles is positioned along a ??? vector passing through two pyrrole rings. This is opposite to the situation of the frequently used 5,15-A2BC porphyrins where the dipole moment is oriented along a meso-meso axis. We have elaborated syntheses of the 5,10-A2B2 porphyrins using transition metal catalyzed transformations of 5,10-A2 porphyrins or direct substitutions reactions thereof which give the target molecules in 22-77 % overall yield. The compounds exhibit interesting structural, spectroscopic and optical features and can serve as building blocks for new porphyrin arrays and applications.
PUBLISHED
Keywords: Porphyrins